Leitura de textos orais de opinião: ensino da argumentação a partir de um protótipo didático de ensino - Batista, Jean Santos (2024)
This research, within the scope of the Professional Master's Program in Letters (Profletras-UFS), aims to deepen the study of reading oral opinion texts with students in the final years of elementary school. Thus, the main objective is to systematize the argumentative reading of this genre through a teaching prototype, whose intervention application occurred in a ninth-grade class at a public school in São Cristóvão, Sergipe. This study is based on the identification of some gaps in studies of oral argumentation in Profletras, observed in a systematic literature review. It was found that work on oral argumentation in schools has often been limited to the application of didactic sequences around the debate genre. In the present proposal, we chose to develop a teaching prototype, according to Rojo (2017), as it is a didactic resource favorable to the integration of media that facilitate work with oral opinion text. The conception of discourse genres defined by Bakhtin (2016); the perspective of interactional argumentation, according to Plantin (2008); the procedures for analyzing argumentative levels, as proposed by Padilla, Douglas, and López (2011); and the principles of argumentative reading proposed by Azevedo, Reis, and Monte (2021) also underpin this research. Methodologically, this research is qualitative in nature, based on BortoniRicardo (2008), and resorts to action research, based on Tripp (2005), for the application of the invention process in the school. Thus, this investigation aligns with the Pedagogy of Multiliteracies, of the New London Group (1996, 2000), and with studies of argumentation in contemporaneity, as well as aiming to contribute to the improvement of the reading skills of the students involved in this intervention proposal. With the application of the research product, the results obtained indicate that the articulation between argumentative reading and the teaching prototype favors students' understanding of oral opinion texts, as well as contributing to the identification of aspects of orality and argumentation. Thus, it is concluded that this approach enables work with oral argumentation in the teaching-learning process.